Finanzas emprendedoras, valoracion, inversión y gobierno en empresas nacientes. - Almeida Blacio, Jorge Hernan; Cueva Jiménez, María Gabriela; Taco Almachi, Fulton Geovanny; Moncayo Lomas, Jessica Geovanna; Casanova Villalba, César Iván; Herrera Sánchez, Maybelline Jaqueline (Editorial Grupo AEA, 2026)
The book presents a practical and strategic guide to entrepreneurial finance for startups and SMEs, emphasizing that financial discipline determines survival and growth in uncertain environments. It explains how accounting and financial statements allow you to “read” the business, focusing on liquidity and cash flow as critical variables. It covers the life cycle of the company: financial foundations, control and planning, through to expansion decisions. It develops the valuation of ventures, showing why traditional methods do not always fit and proposing adapted approaches that combine quantitative estimates, qualitative criteria, and scenario analysis. It then compares sources of financing: equity, bank debt, non-bank alternatives, angel investors, venture capital, crowdfunding, and public programs, highlighting costs, conditions, dilution, and effects on control. It also addresses risk assessment and investment selection using indicators, sensitivity, contingencies, and criteria for decision-making under uncertainty. Finally, it incorporates corporate governance and ethical finance, highlighting transparency, accountability, and sustainability (ESG) as pillars for building trust and attracting capital. Overall, the text offers tools for planning, negotiating, and managing resources rigorously, aligning financial decisions with consistent value creation. It includes examples, recommendations, and implementation paths.